Senam, Screening Serta Pelatihan Keterampilan Fisik dan Kognitif Lansia di Puskesmas Pakan Rabaa Kecamatan Lareh Sago Halaban Kabupaten 50 Kota - Yeffi Masnarivan; Ezzha Elfansdha Putri; Fathiya Aulia Ramadhan; Marsha Fidela Lubis; Sausan Akbari Affa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Health center Pakan Rabaa in District 50 City faces obstacles in achieving the Minimum Service Standard (SPM) for elderly health, recorded as the second lowest rank out of 11 health centers. Community service initiatives were carried out to empower the elderly and increase the independence of elderly ADLs through health screening activities, elderly gymnastics, and physical and cognitive skills training. Activities involved health centers, integrated healthcare centers, and cadres. The goal was to improve health services and target coverage of SPM for Elderly Health in the Pakan Rabaa Health Center area. Methods involved physical gymnastics, brain gymnastics exercises, and ADL, Mental, and BMI screening. Screening results showed more likely with independent ADL status. The depression scale is standard, while the average BMI is close to mild obesity, but many are under normal conditions. More than 50 seniors participated in gymnastics, creating positive experiences, encouragement, and opportunities to share experiences. ADL and depression screening activities can be continued using the g-form. It is important to regularly schedule gymnastics activities and train in physical and cognitive skills to improve the achievement of screening targets at the health center and SPM for Elderly Health Services in the area.